Measuring soccer technique with easy-to-administer field tasks in female soccer players from four different competitive levels - Pedersen, A. V.; Loras, H.; Norvang, O. P.; Asplund, J. (Perceptual and Motor Skills, 2014)
Soccer is a multidimensional sport that requires skills in many different domains. Reports from competitions at the highest levels around the world suggest that a particularly decisive performance factor is a team's technical execution. Testing of technical skills in soccer has been infrequent compared with testing of physiological variables, and there has been a lack of consensus as to which tasks should be included in test batteries. In this study, the validity of four field tasks (heading, long pass, juggling, and hit-the-post) was examined by testing 108 female soccer players from four different competitive levels, representing a hierarchy of skill levels. Correlation analysis indicated that the tasks' results appeared statistically unrelated (Spearman's = .36). Statistical comparisons across competitive levels showed that task performance was closely correlated with players' competition level, with regression analysis indicating that 92% of the variance in mean rankings across tasks could be explained by competitive level. As the easily administered and low-cost tasks identified differences in technical skills across competitive levels, such tasks appear valid for inclusion in tests of technical skills.